The Influence of Role Conflict on Employee Work Performance with Job Stress as an Intervening Variable in the Regional Financial Management Agency, Income and Assets in Binjai City - Dian Ariani Siregar, Poppy; Isa Indrawan, Muhammad (Lafadz Jaya Publisher, 2023)
This study aims to analyze the effect of role conflict on employee performance with work stress as an intervening variable. This type of research is associative quantitative. The number in this study was 173 employees. The research sample uses the Slovin formula, so the sample used is 121 employees. The location of the research was carried out at the Regional Finance, Revenue and Asset Management Agency Office of the City of Binjai. The research model uses Path analysis, and the measurement tool is Smart PLS version 3.3.3. The results of this study are Role Conflict has a positive and significant effect on Job Performance. Role conflict has a positive and significant effect on work stress. Work Stress has a positive and significant effect on work performance. Role conflict influences work performance through work stress positively and significantly.